Effect of different superovulation stimulation protocols on adenosine triphosphate concentration in rabbit oocytes - Cortell, Carmela; Salvetti, Pascal; Joly, Thierry; Viudes-De-Castro, María P. (2017)
Ovarian stimulation protocols are used usually to increase the number of oocytes collected. The determination of how oocyte quality may be affected by these superovulation procedures, therefore, would be very useful. There is a high correlation between oocyte ATP concentration and developmental competence of the resulting embryo. The aim of this study was to evaluate the effect of follicle stimulating hormone (FSH) origin and administration protocols on oocyte ATP content. Rabbit does were distributed randomly into four groups: (i) a control group; (ii) the rhFSH3 group: females were injected, every 24 h over 3 days, with 0.6 mu l of rhFSH diluted in polyvinylpyrrolidone (PVP); (iii) the pFSH3 group: females were injected every 24 h over 3 days with 11.4 mu g of pFSH diluted in PVP; and (iv) the pFSH5 group: females were injected twice a day for 5 days with 11.4 mu g of pFSH diluted in saline serum. Secondly, the effect of pFSH5 protocol on developmental potential was evaluated. Developmental competence of oocytes from the control and pFSH5 groups was examined. Differences in superovulation treatments were found for ATP levels. In the pFSH5 group, the ATP level was significantly lower than that of the other groups (5.63 +/- 0.14 for pFSH group versus 6.42 +/- 0.13 and 6.19 +/- 0.15 for rhFSH3 and pFSH3, respectively; P < 0.05). In a second phase, only 24.28% of pFSH5 ova developed into hatched blastocysts compared with 80.39% for the control group. A negative effect on oocyte quality was observed in the pFSH5 group in ATP production, it is possible that, after this superovulation treatment, oocyte metabolism would be affected.